Piezoresistive Carbon Foams in Sensing Applications - Kordas, Krisztian; Pitkänen, Olli (Frontiers in Materials, 2019)
Mechanical strain sensing is ubiquitous, found in applications such as heart rate monitoring, analysis of body part motion, vibration of machines, dilatation in buildings and large infrastructure, and so forth. Piezoresistive materials and sensors based on those offer versatile and robust solutions to measure strains and displacements and can be implemented even in acceleration and pressure analyses. In this paper, we overview the most prominent piezoresistive materials, and present a case study on carbon foams as well as on their hierarchical hybrid structures with carbon nanotubes/nanofibers. Our results show highly non-linear electrical resistance and mechanical stress dependence on uniaxial strain in both types of materials up to 50% compression. The Young's moduli increase with compressive strain between 1–65 and 0.1–92 kPa for the foam and hierarchical structure, respectively. The foams have giant gauge factors (up to −1000) with large differential gauge factors (on the scale of −10) and differential pressure sensitivity of 0.016 Pa−1 (at 10% strain) making them suitable for detecting both small and large displacements with excellent accuracy of electrical readout as we demonstrate in detecting building wall displacement as well as in monitoring heart rate and flexing of fingers.